Possible shunt compensation strategies based on Conservative Power Theory - Paredes, Helmo K. M.; da Silva, Luiz C. P.; Brandao, Danilo [UNESP]; Marafão, Fernando Pinhabel [UNESP] (Wydawnictwo Sigma-n O T Sp Z O O, 2011)
Considering the Conservative Power Theory (CPT), this paper proposes some novel compensation strategies for shunt passive or active devices. The CPT current decompositions result in several current terms (associated with specific physical phenomena), which were used for the definition of different selective current compensators, in terms of minimizing particular disturbing effects. Simulation results have been demonstrated in order to validate the possibilities and performance of the proposed strategies for single and three-phase four wired circuits.
Keywords: active power filters; harmonic compensation; selective compensation; unbalance compensation